American universities abroad : the leadership of independent transnational higher education institutions - Purinton, Ted; Skaggs, Jennifer (American University in Cairo Press, 2017)
Across the globe, American-style and liberal arts universities are being established. From the first, the American University of Beirut, established in 1866, to the liberal arts institutions being established in Saudi Arabia, Ghana, and elsewhere in the twenty-first century, there is a clear sense of the global desire for the American approach to higher education as a way of counteracting traditional, more narrowly defined university educations. However, these universities operate in a distinctive dynamic that must learn to bridge one culture with another, and leadership of such institutions must by its nature focus on such complexities and tensions. Throughout the chapters of this book, this unique element of these universities will be better understood through the stories and experiences as presented by their presidents, provosts, and other academic leaders.